AI, SCIENTIFIC ARTICLES, AND PLAGIARISM : A CASE STUDY UIN JAKARTA STUDENTS - Jejen Musfah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
AI progress is not only impact positive for productivity performance academic but also has an impact negative like plagiarism and manipulation of research data . Research objectives This analyze AI use , productivity , and student plagiarism undergraduate and master's degrees at FITK UIN Jakarta. The research method mixture that is quantitative and qualitative . Data obtained through questionnaire namely a Google form filled in by 71 students and documents results research . Research results show student use sources online reference for write work scientific but No leave book print and libraries . AI advances are not will turn off book print and library . They also use ICT and AI assistance for make work scientific , will but a number of from they do plagiarism in a way aware . The use of AI must be accompanied by awareness ethics academic . The solutions offered is training ethics academic and skills write , strengthen role lecturers and policies campus like sanctions to deliberate plagiarism . Concern lecturers and campus can prevent plagiarism . Recommended campus build digital infrastructure at once add collection library with books new . Recommended study next focus about forms plagiarism in work scientific student.